Managing herbivory over space and time: consequences for vegetation and cattle responses in African rangelands - Venter, Alexander S (Department of Biological Sciences, 2019)
Mammalian herbivory is integral to determining vegetation structure, composition and ecosystem function in African rangelands, however the extent to which managing the movement of herbivores, specifically livestock, over time and space can sustain functioning and productive rangelands remains unclear. Previous research on forms of rotational grazing management are criticized for being limited to small-scale experimental trials that make untested assumptions about the effect of grazing density on animal behaviour and neglect measurements of landscape-scale pattern and process. Despite this, advocates of holistic planned grazing, a form of high density rotational grazing, claim that their practices can increase rangeland productivity and reverse climate change while doubling stocking rates. Thus, I tested the hypothesis that concentrating herbivores over space and moving them adaptively, primarily through forms of high density rotational grazing management, will reduce the overgrazing of palatable vegetation, increase vegetation cover and thereby enhance rangeland productivity. Given that the functional composition of herbivory over Africa has been simplified to one dominated by grazers, namely cattle, I first explored evidence from paleoecology, historical literature and savanna ecology to test the hypothesis that mid-Holocene African savannas were dominated by herbivory as a means of cycling nutrients and changing vegetation whereas fire perhaps played a lesser role than it does today. Currently, fire consumes 5.8 times more vegetation than herbivores do across sub-Saharan Africa, and charcoal deposits along with early colonial records suggest that herbivory was more prevalent in the past. I argue that the current balance might be shifted toward herbivory, fulfilling the functional role that fire plays in removing old biomass, while releasing less soil carbon and nitrogen to the atmosphere. However, shifting ecosystems to herbivore-dominance has been implicated in switching savannas into tree-dominated alternative stable states, characteristic of woody plant encroachment (WPE) although this has not been tested at regional sales. Using three decades of satellite imagery, I found that woody plant cover has increased by 8% over sub-Saharan Africa and a diversity of drivers, other than CO2, were able to explain 78% of the spatial variation in this trend. High browser densities as well as high and/or low grazer densities have mitigated WPE, while declines in burned area along with warmer, wetter climates have driven WPE. To further explore the nuances of herbivore densities on vegetation change, I used an experimental trial in the grasslands of the Eastern Cape, South Africa, to isolate grazing from other disturbance and climatic drivers. I compared management practices including season-long grazing (SLG), four-camp grazing (FCG) and holistic planned grazing (HPG). These treatments, reflecting a range of grazing densities (SLG < FCG < HPG) at a constant stocking rate, were applied over a period of 2.5 years in an experimental trial in a mesic grassland of South Africa. Cattle gained on average 0.2 ± 0.02 kg day-1 ha-1 and this did not differ between treatments. Grazing management had little effect on cattle herding and grazing behaviours including distance to neighbour (4.8 ± 2.6 m), proportional grazing time (37 ± 1.7 %), trampling (11 ± 2 steps m-2 ), or plant species selection. At the grazing camp scale, HPG did, however, reduce selective foraging behaviour relative to SLG and consequently homogenized vegetation greenness as measured by the normalised difference vegetation index (NDVI). Cattle concentrations under SLG facilitated a reduction in the formation of bare ground by 6 ± 0.4 % on high nutrient, moist soils, however this effect was not apparent on relatively nutrient poor soils or under FCG or HPG. An experimental increase in defoliation frequency and severity on vegetation patches and potted grass plants reduced productivity, particularly in so-called unpalatable species, although this effect was mitigated with nutrient or dung addition. Overall, rotational grazing management did not enhance vegetation productivity or cover relative to less rotational practices. To address the limitations of drawing conclusions from shot-term grazing experiments, I performed a nation-wide farm management survey and a fence-line contrast study between farms that were largely aligned with HPG principles and their respective neighbours. Stocking rate, grazing density, and herbivore type had no consistent effect on remotely sensed NDVI, fractional bare ground, grass or woody plant cover. This thesis presents evidence that vegetation and cattle productivity are largely unaffected by forms of rotational grazing management. Due to high infrastructure costs, adopting HPG might stunt farm profitability relative to alternative management practices in mesic grasslands. However, depending on the farm management goal, HPG may be used to homogenize vegetation cover, while free-ranging cattle under SLG show potential to increase vegetation heterogeneity and cover where soil nutrients are not limiting, akin to the establishment of grazing lawns in savannas. The continental increase in woody plant cover reported here confirms global greening trends and challenges widely held theories about declining terrestrial carbon balances and desert expansion. While climatic drivers like CO2 may enhance the risk of WPE, incorporating browsers and fire along with grazers might mitigate WPE.